Exploring Public Perceptions of Online Project Management Courses: A Qualitative Analysis of Quora Discussions - Brilliant Fajar Muhammad Thomas; Radiktya Dewanto Cahyolaksono; Azizah Hasina Zahrah (AIBPM Publisher, 2025)
The growing demand for professionals with project management skills and the low success rate of projects have pushed the growth of online project management courses. While these courses offer flexibility and accessibility, concerns arise regarding their credibility and practical effectiveness. This study explores public perceptions of online project management courses through discussions on Quora. Implementing a qualitative approach, 20 relevant questions and 129 responses were collected and analyzed through thematic analysis with LiGRE software. Framing Theory and Expectancy-Value Theory are used to support the interpretation of findings. Results indicate eleven themes, which complement the finding that the majority of respondents viewed certifications as useful for credibility and early career entry but questioned their long-term worth compared to real-life experience and soft skills. The findings suggest that course providers must emphasize practical applications, recognized partnerships, and broader competencies to improve trust and relevance to the working environment. This study contributes by showing how external framing and individual motivations shape learner decisions in online project management education